Design and simulation of bi-directional DC-DC converter with dual switch forward snubber. (2019) - Kunalkumar, Bhatt; Gupta, R.A.; Gupta, Nitin
A novel isolated bi-directional buck-boost converter is presented for energy storage application. Isolated boost bi-directional DC-DC converters are required to meet the wide voltage variation demand. The conventional isolated boost converters have some auxiliary circuits to provide an auxiliary path for mismatch current between source inductance and leakage inductance of the transformer. The dual switch forward snubber circuit is adopted as auxiliary circuits along with dual active bridge (DAB) converter in the proposed converter. The proposed converter has distinct advantages like zero voltage switching starting (ZVS), no voltage stress on main switches, no additional conduction losses and improved efficiency as compared to RCD snubber-based converter system. The wide voltage variation in output side for 45V to 320V bi-directional DC-DC converter has been simulated with PSIM. The charging mode and discharging mode with energy storing mode has been explained in detail. The simulation results show the effective performance of proposed converter system. The loss comparison has been shown between RCD snubberbased converter and dual switch forward snubber which proves that dual switch forward snubber has high efficiency compared to RCD snubber circuit.